The influence of islamic spiritual mentoring and religious character on learning outcomes in islamic religious education at state senior high school 1 mojolaban - Sabila Nurul Azizah; Muhammad Ja’far Nashir (At Turots: Jurnal Pendidikan Islam, 2025)
The development of religious character education has become one of the crucial aspects in efforts to form a generation that is not only intellectually intelligent but also possesses moral and spiritual integrity. This study aims to examine the contribution of Islamic spiritual mentoring activities and religious character to the learning achievement of Islamic Religious Education (PAI) among students at State Senior High School 1 Mojolaban in the academic year 2024/2025. This research employs a quantitative approach with a correlational survey method. The population of this study consists of all students participating in Islamic Spiritual Activities (Rohis) totaling 136 individuals, with a randomly selected sample of 73 students. Data collection instruments include questionnaires, documentation, and student report cards. Data analysis was conducted using Pearson correlation test and multiple linear regression. The results indicate that the implementation of mentoring activities and the level of students' religious character are in the moderate category. Students' PAI learning achievement also shows moderate to high categories. However, statistical test results demonstrate that there is no significant influence, either partially or simultaneously, between Islamic spiritual mentoring and religious character on PAI learning achievement. The coefficient of determination is only 0.1%. These findings imply that the formation of religious character and improvement of PAI learning outcomes require a more integrative approach, involving the roles of teachers, families, and the educational environment comprehensively. This research encourages evaluation and strengthening of mentoring activities and their integration into the formal learning system.